PERFORMANCE IMPROVEMENT OF SHARP CRESTED OBLIQUE WEIRS BY USING VEINS - AAREF, NAEEMA THAHER; NOORI, BAHZAD MOHAMMAD ALI (Journal of Duhok University, 2021)
The current research aims to get better performance and capacity of discharge of sharp crested oblique weirs by providing veins perpendicular to weir crest in order to deflect the water jet perpendicular to the weir axis. Seven weir models have been constructed and experimented in which the weir height and the oblique angle are kept constants as (P = 25cm) and (α = 40o), respectively, during the whole experimental work. Three oblique weir conditions are tested, the first one was testing oblique weir with no veins, while, the second condition was by providing one vein at the middle of crest length and changing vein height three times as (Pv = 25, 20 and 15cm) and the third condition studied was by providing two veins to the oblique weir. From the study of surface profiles, it was realized that the maximum X-distance for the water depth above crest to become horizontal was X = 4.93h from the center of oblique weir with no veins, while, X = 4.59h for oblique weir equipped with one vein and X = 4.93h for oblique weir equipped with two veins (h = upstream water depth above crest). The results of discharge coefficient showed that the ratio of vein height to oblique weir height (Pv/P) has a major role on increasing the discharge coefficient and it was observed that the ratio (Pv/P = 0.6) offers the best performance of the weir. A straightforward power equation is recommended for the relation of (Cd) with (h/P) for sharp crested oblique weir equipped with two veins with high correlation coefficient and low mean percentage error. The capacity of discharge of the oblique weir was increased by 69.6% for a weir equipped with one vein, while, the discharge capacity was increased up to 73.5% for a weir equipped with two veins. The limitations of this study are that testing one oblique angle and keeping the weir height as constant for the range of (h/P) between 0.08 and 0.32.